The Turbanned Woman: Strong Gender Consonance in Sikhism - Parneet Brar, Dr. Prabhdeep Kaur Brar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
When he ordained the ‘Khalsa’ or the ‘Pure’, the Tenth Guru of the Sikh religious following, Guru Gobind Singh, gave uniformity to the socio-cultural presence of a new order of humanity. He designated all the men of the ‘Khalsa’ collectivity to be a ‘Singh’ or ‘Lion’ and all the women to be a ‘Kaur’ or a ‘princess’. The women, when they were married to a ‘Singh’, became a ‘Singhni’ or ‘Lioness’. This thought process had a simple yet profound ideology based approach to the turbulent and oppression promotive times. Civil strife and plunder threatened peace and prosperity. In one stroke the divide of male and female was balanced by the visionary act. For generations and in a number of communities there existed strong divisive forces between the sexes. It was for the first time that the social bindings of gender roles were dissolved and the potential of women highlighted from being home-makers to decision-makers. The women who were often eulogized as the ‘honour’ of the turban had in one stroke, after a wide variety of experiences gone on to wearing the turban and donning the mantle of authority for themselves. This paper examines the 21st century perceptions of the world youth on the wearers of the turban. It is an explanation of the Sikh beliefs as a common following and ideology as a people.